Elevation-layered dendroclimatic signal in eastern Mediterranean tree rings. (13th April 2016) - Touchan, Ramzi; Shishov, Vladimir V; Tychkov, Ivan I; Sivrikaya, Fatih; Attieh, Jihad; Ketmen, Muzaffer; Stephan, Jean; Mitsopoulos, Ioannis; Christou, Andreas; Meko, David M
Abstract: Networks of tree-ring data are commonly applied in statistical reconstruction of spatial fields of climate variables. The importance of elevation to the climatic interpretation of tree-ring networks is addressed using 281 station precipitation records, and a network of 79 tree-ring chronologies from different species and a range of elevations in the eastern Mediterranean. Cluster analysis of chronologies identifies 6 tree-ring groups, delineated principally by site elevation. Correlation analysis suggests several of the clusters are linked to homogenous elevational moisture regimes. Results imply that climate stations close to the elevations of the tree-ring sites are essential for assessing the seasonal climatic signal in tree-ring chronologies from this region. A broader implication is that the elevations of stations contributing to gridded climate networks should be considered in the design and interpretation of field reconstructions of climate from tree rings. Finally, results suggest elevation-stratified tree-ring networks as a strategy for seasonal climate reconstruction.